Produção de arroz vermelho manejado organicamente sob irrigação localizada e densidade de plantio - Lira, José Flaviano Barbosa de (Universidade Federal Rural do Semi-Árido, 2015)
The study was conducted at the Federal Institute of Rio Grande do Norte, in Ipanguaçu-RN, to determine the technical feasibility of planting and behavior of red rice (Oryza sativa L.) yield components under drip irrigation, organic management and different planting densities. The treatments consisted of the number of plants per hole (1, 3, 5, 7 and 9) which were tested in a randomized block design with five replications. The variables analyzed were: number of tillers per hill, plant height, number of panicles per plot, average panicle mass, numbers of filled and of empty grains, percentage of empty grains, mass of one hundred grains and yield. Conclusions appoint the technical feasibility of the red rice crop and indicate the density of one plant per hill as the most appropriate for the site, the planting configuration employed, drip irrigation and organic management of red rice
Red rice production under organic management, drip irrigation and planting densities
Keywords: Rice; Organic agriculture; Planting density; Localized irrigation; Arroz; Agricultura orgânica; Densidade de plantio; Irrigação localizada; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO